1997
DOI: 10.1017/s0950268896007352
|View full text |Cite
|
Sign up to set email alerts
|

Epidemic cholera among refugees in Malawi, Africa: treatment and transmission

Abstract: Between 23 August and 15 December 1990 an epidemic of cholera affected Mozambican refugees in Malawi causing 1931 cases (attack rate = 2.4%); 86% of patients had arrived in Malawi < 3 months before illness onset. There were 68 deaths (case-fatality rate = 3.5%); most deaths (63%) occurred within 24 h of hospital admission which may have indicated delayed presentation to health facilities and inadequate early rehydration. Mortality was higher in children < 4 years old and febrile deaths may have been associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
75
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 15 publications
3
75
0
Order By: Relevance
“…The fact that 67% of such patients in our study who provided specimens had stools yielding V. cholerae O1 validates the use of this definition. The antimicrobial susceptibility patterns we observed were similar to those seen in recent East African cholera epidemics 3 (CDC, 1998 unpublished data).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The fact that 67% of such patients in our study who provided specimens had stools yielding V. cholerae O1 validates the use of this definition. The antimicrobial susceptibility patterns we observed were similar to those seen in recent East African cholera epidemics 3 (CDC, 1998 unpublished data).…”
Section: Discussionsupporting
confidence: 82%
“…1 In addition, 6,216 deaths were reported, representing a case fatality rate of 5.7% and accounting for 93% of all reported cholera deaths worldwide. 1 Cholera is essentially a disease of poor sanitation, and epidemics in Africa have been linked to consumption of food and water from unsafe sources, e.g., drinking or bathing in lakes, 2 drinking river water, 3 eating at large funeral feasts, 4 and eating cold leftover foods. 3 Western Kenya has had several discrete waves of cholera during the seventh pandemic, in 1971-1972, 1980-1984, 1992-1993, and most recently, beginning in 1997.…”
mentioning
confidence: 99%
“…Household water storage in wide-mouthed, uncovered, containers, into which cups or other utensils are dipped to obtain water, has been repeatedly implicated in diarrheal disease transmission. [14][15][16][17] Results of this evaluation also showed that the ability to demonstrate proper handwashing behavior was sustained over three years among program participants and their relatives/ friends. These findings were consistent with at least two other studies that showed sustained handwashing knowledge after a relatively brief intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Outbreaks of cholera have been reported frequently in complex emergencies. 13,14 Few published studies have evaluated preventative or treatment measures for reducing child morbidity and mortality due to diarrhoeal diseases in complex emergencies, although the importance of clean water, appropriate sanitation, and rehydration is established. After a programme to distribute soap in a Malawi refugee camp for Mozambican refugees, households with soap reported 27% fewer episodes of diarrhoea than those without.…”
Section: Diarrhoeal Diseasementioning
confidence: 99%